Natural disasters and growth : evidence using a wide panel of countries (2007)
Large natural disasters (LNDs) are ubiquitous phenomena with potentially large impacts on the infrastructure and population of countries, and on their economic activity in general. I examine the occurrence pattern of several types of disasters on a panel of 113 countries and its relationship with economic growth using data ranging from 1960 to 1996. The disasters are earthquakes, floods, slides, volcano eruptions, tsunamis, wind storms, wild fires and extreme temperatures. The country sample is partitioned in two ways: small, medium and large population; and low, medium and high income. The results suggest a heterogeneous pattern of short and long-term impact of LNDs, depending on the per capita GDP, the size of the countries studied and the type of LND. Overall, and contrary to previous research, LNDs appear to have persistent effects on the rate of GDP growth in the period between 1960 and 1996. These effects range from a decrease of 0.9% to an increase of 0.6%, depending on the type of disaster.